ANALISIS PENGARUH VARIASI HASIL PENGELASAN FCAW ANTARA MATERIAL GRADE A TERHADAP MACRO STRUCTURE TEST DI INSERT PLATE SHIP DECK RAMAH LINGKUNGAN - Purwanto, Purwanto; Wa’adduulloh, Mu’izzaddin; Widdo, Risriki (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2024)
Welding has a very important role in engineering and metal production repairs. This is very reasonable because every construction can hardly be separated from metal which involves welding elements. Metal is widely used because it has several advantages, including being strong, rust-resistant, resistant to wear and tear and the raw materials are very economical. The development of technology and science has also had an impact on the increasing demand for metal connections of different types. Several industries that use joining by welding different types of metal include the transportation industry, car manufacturing, shipping and airplanes. One thing that can be done is connecting different types of metal which can be applied in the shipping industry. This research aims to determine the impact of variations in welding FCAW Grade A material 16 mm thick on ship deck insert plates. The use of Flux Core Arc Wellding (FCAW) is often found in the shipping industry. FCAW or what is usually called CO2 arc welding actually includes Metal Inert Gas (MIG) welding, only the protective gas is not only a noble gas such as Argon (Ar) but also CO2 gas or it could be a mixture of the two gases. The FCAW welding process is often used because the protective gas used is CO2 so it is suitable for use in welding steel construction. CO2 decomposes into CO and O2 when in contact with high temperatures. As a result of the high freezing speed, the CO gas produced is trapped in the metal which then forms cavities. Efforts are made to prevent this by providing a mixture of Si and Mn to the electrode so that no gas is trapped and no reaction occurs.